Assistance in Strengthening MSME Financial Records through the Smart Cashier Application - Hamzah Fansuri Yusuf; Agustin Hari Prastyowati; Hayatul Maspufah; Dwi Ratnasari (TGO Journal of Community Development, 2026)
The financial recording assistance activity for MSMEs in Sumberejo Village, Ambulu District, Jember Regency in August 2025 aims to improve business administration skills through the implementation of the Smart Cashier Application. The methods used include the stages of planning, implementation, and evaluation with qualitative-based data analysis. The results of the activity show that MSMEs are able to switch from manual recording to more accurate and structured digital recording. Participants can monitor daily cash flow as well as compile simple financial statements that support business decision-making. The discussion emphasized that mentoring not only provides technical skills, but also forms a new mindset in business management. Technical constraints such as device limitations and differences in initial understanding can be overcome through hands-on methods and intensive guidance. An important finding from this activity is a change in the behavior of MSME actors in managing finances, increasing awareness of transparency, and increasing confidence in running a business. In addition, this activity supports research on the digitalization of MSMEs and shows that community-based interventions are effective in strengthening the foundations of business sustainability. Thus, technology-based assistance is an important strategy to increase the competitiveness of MSMEs at the local level.